Redetermination of the structure of 9,10-dibromoanthracene, C14H8Br2 - Isloor Arun M.; Vijesh A. M.; Gerber Thomas; Hosten Eric; Betz Richard (Zeitschrift für Kristallographie - New Crystal Structures, 2013)
C14H8Br2, triclinic, P1̄ (no. 2), a = 4.0107(1) Å, b = 8.8373(3) Å, c = 16.1148(5) Å, α = 78.658(2)°, β = 83.321(1)°, γ = 80.259(1)°, V = 549.9 Å3, Z = 2, Rgt(F) = 0.0211, wRref(F2) = 0.0526, T = 200 K.